1978
DOI: 10.3168/jds.s0022-0302(78)83622-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Conceptus in the Bovine

Abstract: Growth of fetuses, fetal membranes, and fetal fluids was characterized by least squares analysis for 254 conceptuses ranging from 25 to 278 days of gestation. Prior to 100 days of gestation, increases in allantoic fluid volume and chorio-allantoic membrane weight preceded those of fetal weight, amnio-allantoic membrane weight, and amniotic fluid volume. The relative rate of growth of components suggests a prerequisite of chorio-allantoic membrane expansion for subsequent fetal growth. Male fetuses were heavier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
10

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 9 publications
5
37
0
10
Order By: Relevance
“…The results of the ante-mortem inspection, carried out by the official veterinarian service at the abattoir, were also recorded. Age of fetuses harvested from pregnant cows was estimated from concepti morphology and morphometry (Eley et al, 1978).…”
Section: Measurements and Sample Collectionmentioning
confidence: 99%
“…The results of the ante-mortem inspection, carried out by the official veterinarian service at the abattoir, were also recorded. Age of fetuses harvested from pregnant cows was estimated from concepti morphology and morphometry (Eley et al, 1978).…”
Section: Measurements and Sample Collectionmentioning
confidence: 99%
“…Zmieniały się one sezonowo w zależności od fenologii i warunków śniegowych (Ryc. 4,5). Okres trwania ujemnego bilansu energii w ciągu zimy wynosił 131 dni.…”
Section: C Gates I R J Hudson Wahania Ciężaru Cervus Elaphus Neunclassified
“…Weights of pregnant cows were adjusted for weight of the gravid uterus using data reported for singly-conceived cattle (Eley et al, 1978), domestic sheep (Rattray et al, 1974) and white-tailed deer (Robbins & Moen, 1975). For these species the weigth of the fetus at term represents an average of 57%> of the weight of the total gravid uterus.…”
Section: Weight Measurementmentioning
confidence: 99%
“…Another study on gross examination of bovine fetuses indicated that fetal weight increased significantly over membrane weight just before 100 days of gestation 26 , as shown in Figure 5. However, the placentomes may be less capable of maintaining the aggressive growth of the fetus during the late pregnancy period, which may result in slower fetal growth rate 25 .…”
Section: Relationship Between Development Of Placenta and Fetusmentioning
confidence: 95%